Respons Tanaman Jagung (Zea mays L.) Hibrida Akibat Jarak Tanam Berbeda Pada Sistem Tatam Legowo (2:1) Dan Jenis Pupuk Organik Di Inceptisols Jatinangor. - Agus Wahyudin; Y. Yuwariah; Fiky Yulianto W; A. F. Kevin A (Paspalum: Jurnal Ilmiah Pertanian, 2018)
The objective of this research was to find the best combination of plant spacing and organic fertilizer on the growth and yield of maize (Zea mays L.) Pertiwi-3 in Jatinangor. The experiment was carried outin Ciparanje experimental field on November 2016 to March 2017. The experiment used was Randomized Block Design (RBD) which consisted of  six treatments and four replications, which were the plant spacing  20cmx20xmx75cm + 5t/ha compost, 25cmx25cmx75cm + 5t/ha compost, 30cmx30cmx75cm + 5t/ha compost, 20cmx20cmx75cm + 5t/ha cow manure, 25cmx25cmx75cm + 5t/ha cow manure and 30cmx30cmx75cm + 5t/ha cow manure. The result of the experiment showed that the best result of 100 dry seeds weight was in the treatment of plant spacing 20cmx20cmx75cm + 5t/ha cow manure with a weight of  45,19g. The highest score of Leaf Area Index (LAI) was in the treatment of plant spacing 20cmx20cmx75cm + 5t/ha cow manure score of 2,92 was not significantly different from the treatment of plant spacing 20cmx20cmx75cm + 5t/ha compost with score of 2,82.